"Babad Tanah Jawi" as an Ecological Archive: A Philological Study of Ancient Javanese Manuscripts for Records of Climate and Calamity - Wijaya Wijaya; Zain Nizam; Aiman Fariq (Journal of Humanities Research Sustainability, 2025)
Background. Environmental history in the Indonesian archipelago has often relied on geological data, colonial records, and contemporary environmental reports, leaving indigenous textual traditions underexamined as potential sources of ecological knowledge. Babad Tanah Jawi, a key corpus of ancient Javanese historiographical manuscripts, contains rich descriptions of natural events, celestial signs, and social responses to environmental disruptions, yet its value as an ecological archive has not been systematically explored. Purpose. This study aims to investigate how these manuscripts document patterns of climate variability, environmental calamities, and ecological transformations, and to assess their relevance for reconstructing long-term environmental change in Java. Method. A philological research design was employed to analyze selected manuscript variants through textual criticism, intertextual comparison, and thematic ecological coding. The analysis identified recurrent references to volcanic eruptions, prolonged droughts, exceptional rainfall, crop failures, and shifts in river courses, which align with known geological and climatological data. Results. The findings also highlight indigenous interpretive frameworks that connect environmental disturbances with moral, cosmic, and political meanings, revealing the epistemological foundations through which premodern Javanese societies understood ecological instability. Conclusion. The study concludes that Babad Tanah Jawi offers valuable supplementary evidence for reconstructing historical climate patterns while also enriching contemporary environmental humanities through its integration of cosmology, ecology, and social memory. These insights underscore the importance of indigenous manuscripts as cultural-ecological repositories that can broaden interdisciplinary approaches to climate history, disaster studies, and resilience research.